The legend of Korra. Book four : Balance [videorecording (DVD)] ([Publisher not identified], 2015)
To save the world, Avatar Korra endured her most intense battle yet. Now broken and bruised, Korra begins a journey of self-discovery and survival as the strong prey upon the weak. When an aggressive military force rises up led by the power hungry Kuvira, the fate of the Earth Kingdom hangs in the balance and only the Avatar can set things right.